2003
DOI: 10.1074/jbc.m209807200
|View full text |Cite
|
Sign up to set email alerts
|

Differences on the Inhibitory Specificities of H-Ras, K-Ras, and N-Ras (N17) Dominant Negative Mutants Are Related to Their Membrane Microlocalization

Abstract: RasGTPases include the isoforms H-Ras, K-Ras, and N-Ras. Despite their great biochemical and biological similarities, evidence is mounting suggesting that Ras proteins may not be functionally redundant. A widespread strategy for studying small GTPases is the utilization of dominant inhibitory mutants that specifically block the activation of their respective wild-type proteins. As such, H-Ras N17 has proved to be extremely valuable as a tool to probe Ras functions. However, a comparative study on the inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 53 publications
3
113
0
1
Order By: Relevance
“…Our observation that anchorage-independent growth of NIH 3T3 cells stably expressing K-Ras4B is partially sensitive to FTI although this Ras isoform contains both a methioninecontaining CAAX motif and a polybasic domain, becomes alternatively prenylated, and signals efficiently through Elk-1 in the presence of FTI suggests that H-Ras and K-Ras4B are functionally distinct, a hypothesis for which considerable evi- NARAERRREK CRCV ND dence has accumulated (31)(32)(33)(34)51). In our studies, K-Ras and H-(K 6 )-CVIM appear to induce anchorage-independent growth via incompletely overlapping mechanisms that are not equally affected by FTI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that anchorage-independent growth of NIH 3T3 cells stably expressing K-Ras4B is partially sensitive to FTI although this Ras isoform contains both a methioninecontaining CAAX motif and a polybasic domain, becomes alternatively prenylated, and signals efficiently through Elk-1 in the presence of FTI suggests that H-Ras and K-Ras4B are functionally distinct, a hypothesis for which considerable evi- NARAERRREK CRCV ND dence has accumulated (31)(32)(33)(34)51). In our studies, K-Ras and H-(K 6 )-CVIM appear to induce anchorage-independent growth via incompletely overlapping mechanisms that are not equally affected by FTI.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may result from functional differences between H-Ras and K-Ras4B that are unrelated to prenylation. Several lines of evidence have suggested that H-Ras and K-Ras4B are functionally distinct, possibly related to their different microlocalization (31)(32)(33)(34). If this is the case, K-Ras4B-induced soft agar colony growth may depend more strongly on the function of other farnesylated proteins (35,36) that are themselves sensitive to FTI, whereas H-Ras-induced colony growth may rely less on other farnesylated proteins.…”
Section: Design and Construction Of Mutant Ras Proteins-in Order Tomentioning
confidence: 97%
“…[8] More recently, thanks to the pioneering work of M. Philips, it was demonstrated that Ras was also present and active in endomembranes like the endoplasmic reticulum (ER) and the Golgi complex (GC). [9,10] The three Ras isoforms were also detected in endosomes [11,12] and mitochondria [13][14][15] (for a review see ref. 16).…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…It was initially believed that Ras signaling occurs exclusively at the plasma membrane, but since the discovery of active Ras in the endoplasmic reticulum and Golgi complex, 43,44 all 3 Ras isoforms have been detected in endosomes [45][46][47] and mitochondria. [48][49][50] Thus, Ras isoforms cannot be considered stationary but translocate between cellular compartments. The presence of Ras in multiple cellular locations must have consequences for the regulation of Ras activation and inactivation.…”
Section: Subcellular Localization Of Ras Signaling Complexesmentioning
confidence: 99%